DIETARY FACTORS AFFECTING FIRMICUTES AND BACTEROIDETES RATIO IN SOLVING OBESITY PROBLEM: A LITERATURE REVIEW - Deandra Ardya Sutoyo; Dominikus Raditya Atmaka; Lisandra Maria G. B. Sidabutar (Media Gizi Indonesia, 2020)
Obesity is caused by several factors. Gut microbiota composition is known to be one of the factors to play a role in modulating the obesity process. Nutrient factors and bioactive compounds from food can infl uence and help in modifying the gut microbiota composition, especially Firmicutes and Bacteroidetes. The purpose of this article is to discuss how signifi cant the role of nutrients and other bioactive compounds on Firmicutes and Bacteroidetes ratio in solving the obesity problem. This article was compiled based on the literature search in the last ten years, related to nutrients and bioactive compounds infl uence Firmicutes/Bacteroidetes ratio in obesity. The results from several literature searches provided evidence that alteration in gut microbiota composition was linked to the increase of body weight through metabolic pathways, which was characterized by the increasing number of Firmicutes, the decreased number of Bacteroidetes, and an increase in Firmicutes/Bacteroidetes ratio. The increasing number of Firmicutes could induce short-chain fatty acid (SCFA) production and lead to more energy harvesting. Several dietary factors from fi ber and amino acid, as well as bioactive compounds from an organic acid and polyphenol compounds, could infl uence the gut microbiota composition by reducing the Firmicutes level and increasing Bacteroidetes. The gut microbiota composition, especially Firmicutes and Bacteroidetes, could be induced by modifying diet enriched with fi ber, polyphenol compounds, and other specifi ed nutrients